2010
DOI: 10.1124/jpet.110.171355
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism for Prejunctional Enhancement of Neuromuscular Transmission by Ethanol in the Mouse

Abstract: Ethanol has been shown to have both presynaptic and postsynaptic effects on synaptic transmission. However, the mechanisms by which ethanol affects evoked neurotransmitter release have not been studied at the mouse neuromuscular junction, a synapse at which binomial analysis of neurotransmitter release and measurements of prejunctional ionic currents can be made. Ethanol (400 mM) increased neurotransmitter release independently of both the cAMP and phorbol ester/Munc13 signaling pathways. Binomial analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(56 reference statements)
2
2
0
Order By: Relevance
“…Our voltage-clamp studies further indicate that delayed rectifiers lack sensitivity to ethanol in GoCs. These findings are in general agreement with studies demonstrating that high concentrations of ethanol (>200 mM) are required to inhibit recombinant and native delayed rectifier-type K + channels (Anantharam et al, 1992, Searl and Silinsky, 2010). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our voltage-clamp studies further indicate that delayed rectifiers lack sensitivity to ethanol in GoCs. These findings are in general agreement with studies demonstrating that high concentrations of ethanol (>200 mM) are required to inhibit recombinant and native delayed rectifier-type K + channels (Anantharam et al, 1992, Searl and Silinsky, 2010). …”
Section: Discussionsupporting
confidence: 91%
“…Subthreshold Na + currents, active at voltages between -60 and –70 mV, were detected in rat GoCs and these likely contribute to the generation of the slow pacemaker depolarization preceding the spike threshold (Forti et al, 2006). Several studies have shown that ethanol acutely inhibits or has no effects on Na + channels but we are not aware of any studies on subthreshold Na + channels (Habuchi et al, 1995, Shiraishi and Harris, 2004, Klein et al, 2007, Xiao et al, 2008, Horishita and Harris, 2008, Searl and Silinsky, 2010). Evidence suggests that a specialized, non-inactivating subtype of Na + channels of unknown molecular characteristics mediates subthreshold currents (Taddese and Bean, 2002, Crill, 1996, Bean, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Figure 11A shows representative perineurally recorded responses to intercostal nerve stimulation in control MPS solution and increasing concentrations of cyclohexanol (5-25 mM). As expected, the principal components of the waveform, after the stimulus artefact, comprised a brisk negative deflection -previously associated with inward Na + current at nodes of Ranvier -followed by a larger negative wave, associated with outward current generated by voltage-sensitive K + channels concentrated in presynaptic nerve terminals (Brigant & Mallart, 1982;Penner & Dreyer, 1986;Searl & Silinsky, 2010a). The axonal Na + current was evidently unaffected by cyclohexanol but the nerve terminal K + current was progressively reduced as cyclohexanol concentration was increased.…”
Section: Presynaptic Effects Of Cyclohexanolsupporting
confidence: 66%
“…1984; Zuo et al. 2004; Searl & Silinsky, 2010 a , b ). Overall, aliphatic alcohols potentiate endplate responses at relatively low concentrations but inhibit them at higher concentrations (Cooper & Dretchen, 1975).…”
Section: Discussionmentioning
confidence: 99%